Infection and Death Patterns of COVID-19 Disease in Bangladesh - Muyeed, Abdul; Siddiqi, Md. Nure Alam; Saha, Tushar Kanti; Goni, Md. Abdul (Journal of Health & Biological Sciences, 2020)
Objectives: This study aimed to reveal the prevalence of COVID-19 and investigate the patterns of deaths due to novel coronavirus in Bangladesh. Methods: The data about daily incidences, sex and deaths by the geography of COVID-19 for Bangladesh as of August 29, 2020 have been collected from the daily press releases of the Institute of Epidemiology, Disease Control and Research (IEDCR) and Directorate General of Health Services (DGHS). Case fatality rates (CFR), doubling time, correlation coefficient and graphical presentation were used to investigate the prevalence and patterns of infection and deaths. Results: Infection to tests, recovery to infections and death to infection rates due to novel coronavirus in Bangladesh until August 29, 2020 was 20.25%, 64.37% and 1.36% respectively. The correlation coefficient between daily tests and infections has found 0.978 with a 95% confidence interval 0.971 to 0.984. About 78.46% male and only 21.54% of females have died. Most deaths were found in the Dhaka division (48.26%) and the least deaths in the Mymensingh division (2.12%). The sex ratio of males to females in deaths was 364.23%. The age below 10 has found the least prevalent (0.45%) to deaths and above 60 has found most vulnerable (49.26%) to death. Conclusions: This study showed a strong positive relationship between daily tests and infections. The doubling time of infections and deaths in Bangladesh increased over time maintaining very low differences. Male people are more vulnerable to death compare to females. Aged people are extremely vulnerable to death. The most deaths geographical division is Dhaka and the least deaths in Mymensingh.